Alterações estomatológicas em pacientes portadores de hepatite c e sua correlação com genotipagem do vírus e estado hematológico - Leite Segundo, Airton Vieira (2010)
Objectives: The objective of the present work was to verify the prevalence of oral lesions and salivary flow in patients with chronic hepatitis type C and its correlation with the virus genotype and hematological status of the patient. Methodology: Thirty five patients infected by hepatitis type C virus were analyzed. The evaluation had demographic data, viral subtype, hepatic function and hematological status. The physical exam of the masticatory system took place at the Viral Hepatitis Department of the Amélia da Ponte Health Center, to identify lesions as well as salivary flow in the patient resting and stimulated. Results: The data showed that 60% of the patient were male, 68,8% dun, in the average of 53,9 years old and 74,3% married. The genotype with the greatest incidence was 3 followed by 1, with the period of evolution in the average of 22, 4 months. Ninety four percent of the patients had history of risky behavior. Preexisting surgeries and blood transfusion were the most frequent. Anemia was found in 31, 4% of the patients, leucopenia in 28,6% and alterations in hepatic functions in 54,3% of them. The lesions found were petechias, candidosis, recurrent aphthae ulceration, leukoplakia and glossitis. There was no statistic important relation between the lesion appearance and the hematologic status or the hepatic function. Forty percent of the patients had hyposalivation. Conclusions: There is no correlation of the oral lesions found and reduction of salivary flow with the hematologic status and hepatic function.